1996
DOI: 10.5811/westjem.2018.6.37381
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Computed Tomography Use for Non-traumatic Abdominal Pain: Minimal Variability

Abstract: IntroductionVariability in the use of computed tomography (CT) between providers in the emergency department (ED) suggests that CT is ordered on a provider rather than a patient level. We aimed to evaluate the variability of CT ordering practices for non-traumatic abdominal pain (NTAP) across physicians in the ED using patient-visit and physician-level factors.MethodsWe conducted a retrospective study among 6,409 ED visits for NTAP from January 1 to December 31, 2012, at a large, urban, academic, tertiary-care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The search strategy identified 637 potentially relevant publications. After full‐text review, we found zero studies that provided direct evidence and included 13 studies as indirect evidence 26–38 (Figure 1). These studies were categorized as indirect evidence because none stratify abdominal pain patients into low‐ or non–low‐risk categories, and some include reevaluation of specific pathology identified at the index ED visit, following a positive initial CT, or at an interval less than the 30 days prespecified by the GRACE‐2 expert panel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search strategy identified 637 potentially relevant publications. After full‐text review, we found zero studies that provided direct evidence and included 13 studies as indirect evidence 26–38 (Figure 1). These studies were categorized as indirect evidence because none stratify abdominal pain patients into low‐ or non–low‐risk categories, and some include reevaluation of specific pathology identified at the index ED visit, following a positive initial CT, or at an interval less than the 30 days prespecified by the GRACE‐2 expert panel.…”
Section: Resultsmentioning
confidence: 99%
“…After full-text review, we found zero studies that provided direct evidence and included 13 studies as indirect evidence [26][27][28][29][30][31][32][33][34][35][36][37][38] (Figure 1).…”
Section: Re Sultsmentioning
confidence: 99%
“…Thirteen studies met some criteria and were included as indirect evidence . 12,[46][47][48]74,75,[96][97][98][99][100][101][102] We attempted to abstract the a priori defined outcomes of interest (Box 2), but most studies did not provide these. The reviewers identified four alternative outcomes: 95 1.…”
Section: Interval To Repeat Ctap 30 Days To 12 Months After Index Ctapmentioning
confidence: 99%
“…Zero studies met all criteria for direct evidence. Thirteen studies met some criteria and were included as indirect evidence 12,46–48,74,75,96–102 …”
Section: Questionmentioning
confidence: 99%
See 1 more Smart Citation